The Termination of Middle Criminal Prosecutions based on Restorative Justice - Darma Rejekinta Sembiring; Sri Kusriyah; Peni Rinda Listyawati (Law Development Journal, 2022)
The purpose of this study was to find out and analyze how the form and policy of stopping the prosecution of minor crimes through a restorative justice approach and the obstacles faced in implementing the policy of stopping the prosecution of minor crimes through a restorative justice approach. This study used an empirical legal method by relying on primary data sources. Prosecutor's Regulation No. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice is a breakthrough made by the prosecutor's office to answer legal problems that exist in society, so that punishments that have been considered by the public no longer provide a sense of justice are lost and public trust in the prosecutor's office as part of the public prosecutor's office. Based on the results of the study, it was concluded that of the 80 cases whose prosecution was terminated based on restorative justice referred to above, one of them was carried out by the Demak District Attorney. Although in the implementation of diversion there are obstacles in the form of peace efforts carried out by the Public Prosecutor from the Demak District Prosecutor's Office, the Suspects and Victims have not received a response, but after involving community leaders as mandated in this Perja, peace can be carried out so that a policy is taken to stop the prosecution of the case outside court (before the case is transferred to the Court).